Ян Амос Коменський – основоположник нової прогресивної педагогічної системи, великий гуманіст і мислитель - Кузьмінська, Юлія Олександрівна; Kuzminska, Julia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено дослідження творчої спадщини Яна Амоса Коменського, обґрунтовано його внесок у сучасний процес навчання у системі шкільної освіти. Також проаналізовано окремі аспекти педагогічної спадщини та філософських поглядів Яна Амоса Коменського у контексті предмету дослідження. Зроблено висновки щодо актуальності ідей вченого для розвитку сучасної педагогічної науки. In the article the main pedagogical and philosophical works of the John Amos Comenius are analyzed. In this article the author study John Amos Comenius`s concepts and their implications in the field of theoretic didactics noticing their permanence and existence in modern didactics. Studied ideas of John Amos Comenius and outlined the originality and the permanence of certain didactical phenomena, which can be found from 17-th century till nowadays. The separate aspects of his pedagogical inheritance in the context of the article of research are outlined and the actuality of his works is mentioned.
John Amos Comenius – the Founder of a New Progressive Pedagogical System, the Great Humanist and Philosopher.
Keywords: педагогіка; виховання; навчання; принципи; Ян Амос Коменський; освіта; pedagogy; upbringing; training; principles; John Amos Comenius; education